Distributed fault detection for uncertain Lipschitz nonlinear multi‐agent systems in finite frequency domain. (7th June 2022) - Liang, Dingguo; He, Zhichen; Li, Rongchang; Yang, Ying
Abstract: This article focuses on distributed fault detection for uncertain Lipschitz nonlinear multi‐agent systems (MASs). To handle parameter uncertainties, a finite‐frequency H − / H ∞ $$ H_{-}/H_{∞ } $$ unknown input observer (UIO) is designed to formulate the reference residual system and based on it, a robust UIO corresponding to the fault detection system is designed using an H ∞ $$ H_{∞ } $$ model matching approach. In the UIO constructed for one agent, the unknown input composed of faults in the other agents and disturbances in the whole system is partitioned to decouple part of them, which avoids the constraint of the rank condition of UIO and allows for fault detection for more than one faulty agent. The generated residual is sensitive to the corresponding fault while robust against the nondecoupled unknown input and parameter uncertainties, of which the design conditions are transformed into a set of linear matrix inequalities (LMIs). A numerical simulation is conducted to illustrate the effectiveness of the proposed method.